UU RI No.35 Th.1999 ttg perubahan atas UU No.14 Th.1970 ttg ketentuan-ketentuan pokok kekuasaan kehakiman - TUNGGAL, Hadi Setia (Harvarindo, 2002)
UU RI No.35 Th.1999 ttg perubahan atas UU No.14 Th.1970 ttg ketentuan-ketentuan po...